Perancangan Aplikasi Database Persediaan Obat - Yuniar Andi Astuti; Sujarwo Sujarwo; Muhammad Fathoni (Program Studi Sistem Informasi, 2022)
In the development of information technology, database processing systems are increasing. One of the advantages of the drug inventory application is that recording can be done easily, quickly and accurately. From the research conducted, the weakness of the old system is that inventory recording is still done manually, so it is less effective and accurate. Database management makes it easy for everyone to find, store, and delete information quickly and accurately.Keywords: information, accurate, effective